Analisis Pengembangan Strategi Pemasaran Koperasi Karyawan (KopKar) Untag Surabaya - Ir.Mochammad Singgih.MM Anto; Joko Priyono (2477 - 6165, 2022)
In the current era of increasingly rapid and tight competition, every company or MSME business is required to innovate in all fields, one of which is marketing. The higher level of local and global business competition and the conditions of uncertainty force companies or financial institutions to be able to achieve their competitive advantage so that later they will be able to win the competition globally. This forces companies, SMEs or cooperatives, in this case the Surabaya Untag Employee Cooperative has to give more attention to their environment which can affect cooperatives. The formulation of the problems raised in this study are: 1. What are the factors that influence the development of KopKar Untag Surabaya's marketing strategy?,2. What/How is the right marketing strategy that can increase sales of KopKar Untag Surabaya?The research was conducted using a questionnaire to KopKar officials and experts. The research method uses: Strength Weakness Opportunities Threat (SWOT) and Analytical Hierarchy Process (AHP). From the results of the study obtained several strategies that can be carried out by KopKar Untag Surabaya, namely: (1). Incessantly making breakthroughs in development by seeking and collaborating with outside parties who can quickly make KopKar progress, including with distributors of trendy and quality products, etc. (2). Easy access for the general public to the KopKar exchange. (3). Increase the variety of stock/store product variants. (4). Immediately use digital marketing. With these steps, the development of marketing development will be carried out effectively, efficiently and successfully.